Guidelines for dealing with predatory publishers/publishing: A working document - Col, Valentina de; Garruccio, Maria; Giampieri, Francesca; Jani, Sara (2022)
The phenomenon of predatory publishing and publishers is a challenge that needs to be addressed, as it undermines the quality of scientific endeavor and practice. This publication aims to provide practical guidance on how to avoid predatory publishing to support CGIAR researchers, repository managers, librarians, and staff involved in the quality assurance of publications.